Lucky break - Carter, Brooke, 1977- (Orca sports., 2018)
Lucy "Lucky" Graves is devoted to her championship rugby team. But her dreams of a scholarship are destroyed when she breaks her leg during an important game. If it doesn't heal properly, Lucy could be benched for the rest of the year. What is she supposed to do without rugby?